Optimasi IPSec Site to Site VPN Mikrotik menggunakan Algoritme Enkripsi Blowfish - Ikhwanul Kurnia Rahman; Dadang Iskandar Mulyana; Yuma Akbar (Progresif: Jurnal Ilmiah Komputer, 2023)
Although data security is very important, the performance of a VPN (Virtual Private Network) must also be a concern. This paper presents how the use of encryption algorithms affects the performance of a site-to-site VPN. This research simulates a site-to-site IPsec VPN network using the EVE-NG simulator to run two point-to-point network security encryption algorithms, namely IPSec with the default encryption algorithm AES (Advanced Encryption Standard) and IPSec (Internet Protocol Security) with the Blowfish encryption algorithm to encrypt traffic. data sent over a public network. Test uploading a file of 900 Megabytes from computer 2 and computer 3 to the FTP (File Transfer Protocol) Server with a throughput of 3.51 MBps with the AES encryption algorithm; and 3.81 MBps throughput with the Blowfish encryption algorithm. Traffic does not experience problems on the network or Request Time Out (RTO) with an average ping latency of 8ms on the IPSec network with the AES encryption algorithm; and 7ms on an ipsec network that uses the Blowfish algorithm. The test results show that the Blowfish encryption algorithm has better performance in throughput and latency than using the AES encryption algorithm.Keywords: Virtual Private Network; Internet Protocol Security; Mikrotik; Blowfish Algorithm AbstrakMeskipun keamanan data sangat penting, akan tetapi performa VPN (Virtual Private Network) juga harus menjadi perhatian. Paper ini menyajikan bagaimana penggunakan algoritme enkripsi mempengaruhi performa dari site to site VPN. Penelitian mensimulasikan jaringan site to site IPsec VPN menggunakan simulator EVE-NG untuk menjalankan dua algoritme enkripsi keamanan jaringan point to point, yaitu IPSec dengan algoritme enkripsi default AES (Advanced Encryption Standard) dan IPSec (Internet Protocol Security) dengan algoritme enkripsi Blowfish dalam mengenkripsi trafik data yang dikirim melalui jaringan publik. Uji upload file sebesar 900 Megabyte dari komputer 2 dan komputer 3 ke FTP (File Transfer Protocol) Server dengan throughput 3,51 MBps dengan algoritme enkripsi AES; dan throughput 3,81 MBps dengan algoritme enkripsi Blowfish. Trafik tidak mengalami kendala pada jaringan atau Request Time Out (RTO) dengan latency ping rata-rata 8ms pada jaringan IPSec algoritme enkripsi AES; dan 7ms pada jaringan ipsec yang menggunakan algoritme Blowfish. Hasil uji menunjukkan algoritme enkripsi Blowfish memiliki performa lebih baik dalam troughput dan latency dibandingkan menggunakan algoritme enkripsi AES.Kata kunci: Virtual Private Network; Internet Protocol Security; Mikrotik; Advanced Encryption Standard; Algoritme BlowfishAlthough data security is very important, the performance of a VPN (Virtual Private Network) must also be a concern. This paper presents how the use of encryption algorithms affects the performance of a site-to-site VPN. This research simulates a site-to-site IPsec VPN network using the EVE-NG simulator to run two point-to-point network security encryption algorithms, namely IPSec with the default encryption algorithm AES (Advanced Encryption Standard) and IPSec (Internet Protocol Security) with the Blowfish encryption algorithm to encrypt traffic. data sent over a public network. Test uploading a file of 900 Megabytes from computer 2 and computer 3 to the FTP (File Transfer Protocol) Server with a throughput of 3.51 MBps with the AES encryption algorithm; and 3.81 MBps throughput with the Blowfish encryption algorithm. Traffic does not experience problems on the network or Request Time Out (RTO) with an average ping latency of 8ms on the IPSec network with the AES encryption algorithm; and 7ms on an ipsec network that uses the Blowfish algorithm. The test results show that the Blowfish encryption algorithm has better performance in throughput and latency than using the AES encryption algorithm.Keywords: Virtual Private Network; Internet Protocol Security; Mikrotik; Blowfish Algorithm AbstrakMeskipun keamanan data sangat penting, akan tetapi performa VPN (Virtual Private Network) juga harus menjadi perhatian. Paper ini menyajikan bagaimana penggunakan algoritme enkripsi mempengaruhi performa dari site to site VPN. Penelitian mensimulasikan jaringan site to site IPsec VPN menggunakan simulator EVE-NG untuk menjalankan dua algoritme enkripsi keamanan jaringan point to point, yaitu IPSec dengan algoritme enkripsi default AES (Advanced Encryption Standard) dan IPSec (Internet Protocol Security) dengan algoritme enkripsi Blowfish dalam mengenkripsi trafik data yang dikirim melalui jaringan publik. Uji upload file sebesar 900 Megabyte dari komputer 2 dan komputer 3 ke FTP (File Transfer Protocol) Server dengan throughput 3,51 MBps dengan algoritme enkripsi AES; dan throughput 3,81 MBps dengan algoritme enkripsi Blowfish. Trafik tidak mengalami kendala pada jaringan atau Request Time Out (RTO) dengan latency ping rata-rata 8ms pada jaringan IPSec algoritme enkripsi AES; dan 7ms pada jaringan ipsec yang menggunakan algoritme Blowfish. Hasil uji menunjukkan algoritme enkripsi Blowfish memiliki performa lebih baik dalam troughput dan latency dibandingkan menggunakan algoritme enkripsi AES.Kata kunci: Virtual Private Network; Internet Protocol Security; Mikrotik; Advanced Encryption Standard; Algoritme Blowfish